2006
DOI: 10.4489/myco.2006.34.1.014
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of Straw into Improved Fodder: Preliminary Treatment of Rice Straw Using Mechanical, Chemical and/or Gamma Irradiation

Abstract: Crude protein (CP) content of mechanically ground rice straw into small particles by an electric grinder and reducing value (RV) and soluble protein (SP) in the culture filtrate were lower than that of the chopped straw into 5~6 cm lengths when both ground and chopped straws were fermented with Aspergillus ochraceus, A. terreus or Trichoderma koningii, at steady conditions. The reduction rate of RV, SP and CP was 22.2, 2.4, 7.3%; 9.1, 4.9, 8.5% or 0.0, 0.0, 3.6% for the three fungi, respectively. Chemical pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Thes results have been confirmed by the results of Helal [32]; pretreatment before fungal hydrolysis increases the surface area of the cellulose by reducing particle size.…”
Section: Effect Of Different Pretreatment On Total Reducing Sugar Yieldsupporting
confidence: 66%
See 1 more Smart Citation
“…Thes results have been confirmed by the results of Helal [32]; pretreatment before fungal hydrolysis increases the surface area of the cellulose by reducing particle size.…”
Section: Effect Of Different Pretreatment On Total Reducing Sugar Yieldsupporting
confidence: 66%
“…According to Helal [32], ionizing radiation as γ lowers the degree of the polymerization of cellulose and lignin and partially disrupts the ligno-cellulosic complex.…”
Section: Effect Of Different Pretreatment On Total Reducing Sugar Yieldmentioning
confidence: 99%
“…However, without appropriate treatment, a mass of agricultural, industrial and municipal cellulosic wastes has accumulated, resulting in the risk of environmental pollution [ 6 ]. Various methods, such as composting, mechanical treatment and chemical treatment, have been applied to treat these cellulosic wastes [ 7 , 8 ]. Ethanol production from lignocellulosic biomass has received much attention due to the immense potential for conversion of renewable biomaterials into biofuels and chemicals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were shown by wheat straw when treated using gamma rays along with crushing [ 30 ]. A study by Helaln [ 31 ] indicated increase in the contents of reducing sugar (4-fold) and soluble and crude protein after pretreatment of rice straw with gamma radiations followed by its saccharification with A. ochraceus , A. terreus , or T . koningii .…”
Section: Gamma Irradiationmentioning
confidence: 99%